Tikhonov regularization-based operational transfer path analysis. (15th June 2016) - Cheng, Wei; Lu, Yingying; Zhang, Zhousuo
Abstract: To overcome ill-posed problems in operational transfer path analysis (OTPA), and improve the stability of solutions, this paper proposes a novel OTPA based on Tikhonov regularization, which considers both fitting degrees and stability of solutions. Firstly, fundamental theory of Tikhonov regularization-based OTPA is presented, and comparative studies are provided to validate the effectiveness on ill-posed problems. Secondly, transfer path analysis and source contribution evaluations for numerical cases studies on spherical radiating acoustical sources are comparatively studied. Finally, transfer path analysis and source contribution evaluations for experimental case studies on a test bed with thin shell structures are provided. This study provides more accurate transfer path analysis for mechanical systems, which can benefit for vibration reduction by structural path optimization. Furthermore, with accurate evaluation of source contributions, vibration monitoring and control by active controlling vibration sources can be effectively carried out. Highlights: A Tikhonov regularization-based OTPA is proposed to solve ill-posed problems. Both fitting degrees and stability of solutions are considered. Theory analysis, numerical and experimental studies are provided to validate effectiveness. Misjudgments and accuracy of TPA are significantly improved. This study can benefit for vibration monitoring, reduction and control.